Influence of mixing energy and pre-shear on the rheological characterization of cement pastes - Campos, Renan Serralvo [UNESP] (2022)
The analysis of rheological behavior can encompass different materials, including cementitious materials, such as pastes, mortars and concretes, which, in fresh state, behave like fluids. In general, the quality control of these materials in fresh state is carried out through empirical tests that aim to qualify properties such as consistency, fluidity, among others. However, empirical tests are not able to completely characterize the rheological behavior of cementitious materials, being necessary for this to carry out rheometric tests, in which it is possible to obtain the fundamental rheological parameters – viscosity and yield stress – of these composites. Rheological characterization of cementitious materials involves the determination of rheological parameters of complex suspensions, composed of different constituent materials that interact with each other, from a chemical and physical point of view. Other factors, such as equipment geometry, temperature, mixing energy, test protocol, can also influence the determination of the rheological properties of these composites. In this sense, the aim of this study is to evaluate the influence of mixing energy and pre-shear on the rheological properties of cement pastes. For this purpose, samples with water/cement ratios equal to 0.40, 0.45, 0.50, 0.55, 0.60 and 0.65 by weight were studied. Two levels of mixing energy were used: low intensity mixing (maximum rotation equal to, approximately, 270 rpm), with a planetary mixer; and high intensity mixing (maximum rotation equal to, approximately, 12,000 rpm) with a high shear mixer. Two test protocols were established, one with zero pre-shear (resting for 90 s of the sample in the rheometer) and the other with application of a constant shear rate equal to 100 s–1, for 60 s, followed by rest of the material for 30 s. The results indicated that the mixing energy and pre-shear significantly influence the rheological behavior of cement pastes with higher solids volume (w/c ratio ≤ 0.45).